Modernisasi Keagamaan Islam Di Indonbsia (Telaah Pemikiran A. Mukti Ali) (Kontekstualita: Jurnal Penelitian Sosial Keagamaan, 2006)
This article uncovers A. Mukti Ali b thoughts in his efforts to modernize the religious thoughts in Indonesia. All A. Mukti Ali s worl<s are analyze employing analytical critical and historical approaches. A. Mukti Ali is in the opinion of the importance of the religion in national development. So dialog and harmonization among pertaining parties in this countries are of great importance. He also contributes in the establishement of MUI (The Indonesian Council of Ulama) as the representative body for the affairs and interests of Muslim people in Indonesia. He is also credited to the efforts to position Muslims as the capitals no the barriers, of national development.